The use of expressive means of speech in advertising texts of the Soviet and modern periods - Malomoshnova, А.В.; Musinova, Г.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article presents a comparative analysis of expressive means of speech used in advertising texts of the Soviet period (1950s–1960s) and in contemporary media advertising (print and digital). The aim of the study is to identify lexical and stylistic features of advertising texts from different historical periods and to examine the mechanisms of persuasive influence on the consumer. The research is based on comparative, descriptive, and linguopragmatic methods. The material of the study includes ten advertising posters of the Soviet period and nine contemporary advertising texts promoting similar mass-consumption products. The analysis focuses on lexical and stylistic devices such as epithets, metaphors, and periphrases, as well as on syntactic constructions characteristic of advertising discourse, including imperative forms, question–answer structures, nominative and elliptical sentences. The research findings demonstrate that Soviet advertising texts are characterized by restraint, conciseness, and a predominantly informative orientation, with a limited use of expressive means. In contrast, contemporary advertising exhibits an expanded expressive potential, actively employing emotionally charged vocabulary, figurative nominations, psychological techniques of influence, and dialogic strategies aimed at establishing contact with the addressee. A comparative examination of advertising texts from different historical periods makes it possible to identify the influence of sociocultural and ideological factors on the linguistic design of advertising discourse.